La generalización en cartografía básica y temática - Galvis Lagos, María Fernanda (Revista Científica, 2006)
The knowledge and explanation of the spatial organization and its variations is inherent to Geography and constitutes its essence for cartographic expression. Spatial organization can be understood as different scale systems and subsystems boxed hierarchy for which it must be hierarchically classified and represented cartographically in geographic spaces of different sizes giving rise to cartographic generalization. However, by revising cartographic materials produced by different national organizations it is evident that the use of flat classifications obstructs the cartographic generalization process and shows serious concept and procedure difficulties when the cartographic scale is changed. In this paper, therefore, a cartographic generalization concept based on the hierarchical theory and the resolution level notion is outlined, and it is shown how the applied or instrumental vocation of hierarchical classification is the cartographic one, since each hierarchical level needs an enough spatial dimension in order to express itself. Once conceptual basis is defined, a cartographic generalization procedure based on a scalar hierarchical model is posed, that defines the concepts developed in each hierarchy level and the scalar ranks on which each level is represented. Moreover, the correct use of visual variables that reflect information level and hierarchical classification is shown. The preceding proposal is applied in six examples of generalization for thematic cartography, in which, beginning with the higher resolution level, hierarchic classification is basic for making advances tolierarchically higher levels that are represented at smaller scalés.